Procedura finansowania zadań publicznych realizowanych przez organizacje pozarządowe w trybie art. 19a ustawy o działalności pożytku publicznego i o wolontariacie - Księski, Krzysztof (Studia Prawa Publicznego, 2024)
The article discusses the procedure for financing public tasks commissioned by the executive bodies of local government in a non-open competition mode, regulated in Art. 19a of the Act on Public Benefit and Volunteering, which is the basic legal act regulating the functioning of non-governmental organizations in Poland. Commissioning the implementation of public tasks may take the form of entrusting the implementation of a public task or supporting the implementation of a public task. The basic form of commissioning public tasks by local government administration bodies is the competition procedure. It allows the principle of competitiveness and transparency of this process to be maintained. However, the legislator provided for the possibility of commissioning the implementation of public tasks also in a non-competition mode. By creating this possibility of commissioning public tasks, it introduced numerous restrictions for this mode, thanks to which this procedure is secondary to the basic form of commissioning public tasks by way of an open competition. The purpose of the discussion here is to analyze the procedure in matters relating to outsourcing the implementation of public tasks to non-governmental organizations by local government administration bodies within the meaning of the above-mentioned Act in a non-competition manner. The article also contains proposals for amending the regulation in question to adapt it to the currently existing socio-economic relations, because this regulation has been in force for over twenty years and requires changes, which results from the previous experience in its application.